Slow Fashion Orientation and Consumer Attitude on Purchase Intention and Will-ingness to Pay a Premium Price - Tiffany Tiffany; Serli Wijaya; Ferry Jaolis (Master of Management, School of Business and Management, Petra Christian University, 2025)
The rapid growth of the global fashion industry has made it the world’s third highest contributor to waste and pollution. In recent years, the slow-fashion movement has been oriented towards sustainability issues to reduce the negative impact of fast fashion. This study aims to analyze the effect of Slow-Fashion Orientation (SFO) on Attitude, Purchase Intention, and Willingness to Pay Premium. Primary data collection was conducted through a survey of 251 respondents spread across various regions of Indonesia through purposive sampling using the Populix research panel service. The results showed that slow-fashion orientation (SFO) has a direct and significant effect on Attitude, Purchase Intention, and respondents' willingness to pay more for slow-fashion products (Willingness To Pay Premium). Attitude, directly and as a mediator, is proven to significantly influence Purchase Intention, and respondents' willingness to pay more for slow-fashion products (willingness to pay premium).